Redescription and molecular characterization of Panagrellus ceylonensis (Nematoda, Rhabditida, Panagrolaimidae) from India - Heena; Kumar, Nitesh; Chaubey, Ashok Kumar (Zootaxa, 2023)
A species of genus Panagrellus was discovered from a wet season form of an oriental common evening brown butterfly Melanitis leda. In this study, a detailed description of Panagrellus ceylonensis is provided including the morphometry, light microscopy and molecular (18S and 28S rDNA genes) studies. Morphological studies on the species agree with original description and characterized by having 1250–1481µm long body in females and 949–1305µm in males, lateral fields with four longitudinal incisures, lip region continuous and 8–11 µm wide, six offset lips with protruding labial sensilla, neck 124–173 µm long, excretory pore at the level of basal bulb, vulva post-equatorial (V = 68–71), vagina anteriorly orientated with heavily muscled vaginal walls, post-vulval uterine sac 111–135 µm long or 1.7–2.6 times as long as the corresponding body diameter, tail conical elongate with an acute terminus in both sexes, spicule 71–91 µm long, ventrally curved having hooked manubrium and bifurcated lamina tip, lamina ventrally curved with dorsal deflexion at about 60% of spicule length, gubernaculum 26–31 µm long and well developed. Morphologically, the Indian population of P. ceylonensis does not show a significant difference from the type material of P. ceylonensis in the original description. For molecular studies of this species, the sequence of 18S rDNA is obtained for the first time. Phylogenetic trees based on 18S and 28S rDNA sequences are provided in this study. Additionally, bionomics and global distribution of the species of Panagrellus genus are also discussed. In conclusion, our study provides a comprehensive morphological characterisation and molecular marker sequences of 18S, and 28S genes that can be used to support future taxonomical research on this species and emphasizes the importance of combining molecular data with morphological data to describe the species accurately.